Influence of post-weaning management system during the finishing phase on grasslands or feedlot on aiming to improvement of the beef cattle production - Barbero, Rondineli P.; Malheiros, Euclides B. [UNESP]; Nave, Renata L.G.; Mulliniks, John T.; Delevatti, Lutti M. [UNESP]; Koscheck, Jefferson F.W. [UNESP]; Romanzini, Elieder P. [UNESP]; Ferrari, Adriana C. [UNESP]; Renesto, Diego M. [UNESP]; Berchielli, Telma T. [UNESP]; Ruggieri, Ana C. [UNESP]; Reis, Ricardo A. [UNESP] (Elsevier, 2017)
The effects of differing post-weaning management systems applied during the wet season were evaluated on the performance of 108 young Nelore (Bos taurus indicus) bulls finished on grasslands or feedlot system during the dry season. In Exp. 1, three grazing heights (15 cm, 25 cm, and 35 cm) of Brachiaria brizantha (Hochst ex A. Rich) Stapf Marandu were evaluated during the wet season with bulls receiving 0.3% of body weight (BW) in supplementary feed. In Exp. 2, supplementation levels were decreased as grazing heights were increased such as: (1) low height (15 cm) and high supplementation (0.6% BW) (LH–HS); (2) moderate height (25 cm) and moderate supplementation (0.3% BW) (MH–MS); or (3) high height (35 cm) with no supplementation (HH–NS). In both experiments, at the end of the wet season, a half of the bulls were finished on grasslands and receiving 1.0 kg/100 kg BW of dietary supplementation while the remaining bulls were placed in a feedlot system. A non-linear regression test was applied (linear plateau) to estimate the point of stabilization of DMI on feedlot. The experimental design was completely randomized in a factorial arrangement 3 (post-weaning system) × 2 (finishing systems), consisting of three replicates (lots of three bulls) per treatment (n = 18, each Exp.). In the Exp. 1, the post-weaning system using 35 cm of grazing height had greater BW (P = 0.04) through the finishing phase in comparison with bulls grazing 15 cm of grazing height. However, the ADG during the initial 21 days of the finishing phase was changed by grazing height used during the post-weaning phase (P = 0.004), and by finishing system (P = 0.007). The post-weaning system did not alter the carcass weight (P = 0.63), but the bulls finished on grasslands exhibited greater carcass weight (P = 0.02) than bulls finished on feedlot. In the Exp. 2, non-supplemented bulls (HH-NS) took a longer time (± 10%) to DMI stabilization on feedlot (P < 0.01). There were no changes in the carcass weight caused by post-weaning system (P = 0.84), or by finishing system (P = 0.14). The evaluated systems combining increasing grazing height and decreasing supplementation level during the post-weaning phase can be used during the wet season according to the economic background or production target, once these systems do not influence the finishing phase.
Keywords: Beef cattle; Feedlot; Finishing; Grasslands; Post-weaning; Supplementation